N-p-coumaroyloctopamine ameliorates hepatic glucose metabolism and oxidative stress involved in a PI3K/AKT/GSK3β pathway - Huang, Yuechang; Zhang, Xingmin; Li, Qian; Zheng, Wende; Wu, Panpan; Wu, Rihui; Chen, Wen-Hua; Li, Chen (Frontiers in Pharmacology, 2024)
Type 2 diabetes mellitus is regarded as a chronic metabolic disease characterized by hyperglycemia. Long-term hyperglycemia may result in oxidative stress, damage pancreatic β-cell function and induce insulin resistance. Herein we explored the anti-hypoglycemic effects and mechanisms of action of N-p-coumaroyloctopamine (N-p-CO) in vitro and in vivo. N-p-CO exhibited high antioxidant activity, as indicated by the increased activity of SOD, GSH and GSH-Px in HL-7702 cells induced by both high glucose (HG) and palmitic acid (PA). N-p-CO treatment significantly augmented glucose uptake and glycogen synthesis in HG/PA-treated HL-7702 cells. Moreover, administration of N-p-CO in diabetic mice induced by both high-fat diet (HFD) and streptozotocin (STZ) not only significantly increased the antioxidant levels of GSH-PX, SOD and GSH, but also dramatically alleviated hyperglycemia and hepatic glucose metabolism in a dose-dependent manner. More importantly, N-p-CO upregulated the expressions of PI3K, AKT and GSK3β proteins in both HG/PA-induced HL-7702 cells and HFD/STZ-induced mice. These findings clearly suggest that N-p-CO exerts anti-hypoglycemic and anti-oxidant effects, most probably via the regulation of a PI3K/AKT/GSK3β signaling pathway. Thus, N-p-CO may have high potentials as a new candidate for the prevention and treatment of diabetes.